Archives at risk: addressing a global concern. Issue 1 (November 2018) - Boel, Jens; Sutton, David C.
Abstract : Literary archivists in recent years have often taken an interest, and occasionally taken the lead, in projects which concern the multi-faceted topic of "archives at risk". This essay reviews recent thinking and action on archives at risk, with special reference to archives which relate to cultural heritage, and describes practical responses in the three areas of documentary heritage at risk, the papers of dissident authors, and the challenging question of providing safe havens for archives at risk.